GAME TEACHING METHODS FOR FOREIGN LANGUAGE LEARNING IN HIGH SCHOOLS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article's goal is to investigate the methodological and psychological underpinnings of how to organize and employ game components in a university foreign language course taught by a faculty other than philology. The requirements and qualifications for using games as a teaching tool are taken into account. The current categories of game-based learning strategies for foreign language instruction are examined, along with strategies for encouraging students to use these strategies. The primary clauses outlining the game's function as a teaching tool in higher education are put forth.